2022
DOI: 10.3389/fmicb.2022.913436
|View full text |Cite
|
Sign up to set email alerts
|

Empirical vs. Susceptibility-Guided Treatment of Helicobacter pylori Infection: A Systematic Review and Meta-Analysis

Abstract: BackgroundTreating Helicobacter pylori infection according to antibiotic resistance has been frequently recommended. However, information on its real effectiveness is scarce.AimThe aim of this study is to perform a meta-analysis comparing empirical vs. susceptibility-guided treatment of H. pylori.MethodsSelection of studies: Studies comparing empirical versus susceptibility-guided treatment were selected. Search strategy: electronic and manual up to August 2021. Data synthesis: by intention-to-treat (random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 122 publications
0
36
0
2
Order By: Relevance
“…Some authors have demonstrated higher eradication rates with culture-guided therapy compared to empirical treatment (26-28), showing tailored therapy to be the most cost-effective strategy (28, 29). Nyssen et al for rst-line treatments also obtained better e cacy results with susceptibility-guided strategy, but this bene t could not be demonstrated when quadruple regimens were prescribed (30). It is important to consider the risks of prescribing empirical quadruple treatments in selecting resistant H. pylori strains and in their impact on gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated higher eradication rates with culture-guided therapy compared to empirical treatment (26-28), showing tailored therapy to be the most cost-effective strategy (28, 29). Nyssen et al for rst-line treatments also obtained better e cacy results with susceptibility-guided strategy, but this bene t could not be demonstrated when quadruple regimens were prescribed (30). It is important to consider the risks of prescribing empirical quadruple treatments in selecting resistant H. pylori strains and in their impact on gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…115 A recent meta-analysis combined 54 clinical studies to examine the efficacy of tailored therapy as first-and second-line therapy. 116 In this study, tailored therapy had a significantly higher eradication success rate than that of empirical therapy in an integrated analysis that included all eradication regimens (86% vs 76%: RR, 1.12; 95% CI, 1.08 to 1.17). However, there were no differences within the group of primary treatments, and no differences within the group of secondary treatments.…”
Section: Clinical Outcomes Of Tailored Therapymentioning
confidence: 68%
“…Two meta-analyses have shown a benefit in increasing eradication rates when susceptibility-guided treatment was performed [ 36 , 37 ]. However, both demonstrated that better efficacy results occurred only among patients in whom the susceptibility-guided strategy, as opposed to empiric therapy, was implemented for first-line triple regimens—combinations that are no longer considered an ideal empiric regimen.…”
Section: The Role Of Antimicrobial Susceptibility Testing In Clinical...mentioning
confidence: 99%
“…A recent comprehensive meta-analysis reviewed 16 studies (with a total of 1283 patients) of tailored versus empiric therapy for refractory infection [ 36 ]. Most studies were of second-line therapy, and nine of them were randomized.…”
Section: The Role Of Antimicrobial Susceptibility Testing In Clinical...mentioning
confidence: 99%